Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve the given problem step-by-step.
### Part 1: Determine the nature of the roots of the quadratic equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex]
To determine the nature of the roots of a quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex], we can use the discriminant, which is calculated as [tex]\( \Delta = b^2 - 4ac \)[/tex].
For the equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex]:
1. Identify the coefficients:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -4\)[/tex]
- [tex]\(c = 3\)[/tex]
2. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values, we get:
[tex]\[ \Delta = (-4)^2 - 4 \cdot 2 \cdot 3 = 16 - 24 = -8 \][/tex]
3. Analyze the discriminant:
- If [tex]\(\Delta > 0\)[/tex], the equation has two distinct real roots.
- If [tex]\(\Delta = 0\)[/tex], the equation has two equal (repeated) real roots.
- If [tex]\(\Delta < 0\)[/tex], the equation has two complex roots.
Since [tex]\(\Delta = -8\)[/tex] which is less than zero, the quadratic equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex] has complex roots.
### Part 2: Find the values of [tex]\(a\)[/tex] such that the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] has equal roots
For the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] to have equal roots, its discriminant must be zero. Let's find the discriminant for this equation.
1. Identify the coefficients:
- [tex]\(a = 9\)[/tex]
- [tex]\(b = -3a\)[/tex]
- [tex]\(c = 1\)[/tex]
2. Set the discriminant to zero:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the coefficient values, we get:
[tex]\[ \Delta = (-3a)^2 - 4 \cdot 9 \cdot 1 = 9a^2 - 36 \][/tex]
For the equation to have equal roots:
[tex]\[ 9a^2 - 36 = 0 \][/tex]
3. Solve for [tex]\(a\)[/tex]:
[tex]\[ 9a^2 = 36 \][/tex]
[tex]\[ a^2 = 4 \][/tex]
[tex]\[ a = \pm 2 \][/tex]
Therefore, the values of [tex]\(a\)[/tex] for which the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] has equal roots are [tex]\(\boxed{-2 \text{ and } 2}\)[/tex].
### Part 1: Determine the nature of the roots of the quadratic equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex]
To determine the nature of the roots of a quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex], we can use the discriminant, which is calculated as [tex]\( \Delta = b^2 - 4ac \)[/tex].
For the equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex]:
1. Identify the coefficients:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -4\)[/tex]
- [tex]\(c = 3\)[/tex]
2. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values, we get:
[tex]\[ \Delta = (-4)^2 - 4 \cdot 2 \cdot 3 = 16 - 24 = -8 \][/tex]
3. Analyze the discriminant:
- If [tex]\(\Delta > 0\)[/tex], the equation has two distinct real roots.
- If [tex]\(\Delta = 0\)[/tex], the equation has two equal (repeated) real roots.
- If [tex]\(\Delta < 0\)[/tex], the equation has two complex roots.
Since [tex]\(\Delta = -8\)[/tex] which is less than zero, the quadratic equation [tex]\(2x^2 - 4x + 3 = 0\)[/tex] has complex roots.
### Part 2: Find the values of [tex]\(a\)[/tex] such that the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] has equal roots
For the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] to have equal roots, its discriminant must be zero. Let's find the discriminant for this equation.
1. Identify the coefficients:
- [tex]\(a = 9\)[/tex]
- [tex]\(b = -3a\)[/tex]
- [tex]\(c = 1\)[/tex]
2. Set the discriminant to zero:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the coefficient values, we get:
[tex]\[ \Delta = (-3a)^2 - 4 \cdot 9 \cdot 1 = 9a^2 - 36 \][/tex]
For the equation to have equal roots:
[tex]\[ 9a^2 - 36 = 0 \][/tex]
3. Solve for [tex]\(a\)[/tex]:
[tex]\[ 9a^2 = 36 \][/tex]
[tex]\[ a^2 = 4 \][/tex]
[tex]\[ a = \pm 2 \][/tex]
Therefore, the values of [tex]\(a\)[/tex] for which the quadratic equation [tex]\(9x^2 - 3ax + 1 = 0\)[/tex] has equal roots are [tex]\(\boxed{-2 \text{ and } 2}\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.